Cechy reprodukcyjne gęsi ze stad zachowawczych utrzymywanych w półintensywnym systemie chowu - Książkiewicz, Juliusz; Wołoszyn, Janina; Okruszek, Andrzej (Reproductive Traits of Geese from Conservative Flocks Maintained Insemi-Intensive System, 2008)
The reproductive traits of geese from 12 conservative flocks kept in a poultry house with the adjacent pens were analyzed. Production results reached in this semi-intensive system were compared with the results obtained over 8 generations of geese of these conservative flocks maintained in extensive system, i.e. on yards of restricted area, partially shaded and covered with straw, with free access to water and feed. The improved maintenance system of birds resulted in the elongation of laying period to 190 days for the Ga geese, and shortening it to 159 days only for the Pd, an increase of egg set number and laying intensity in all flocks (with the exception of Ga), as well as enlargement of an egg weight, with the exception of Lu, Pd, Ka, Ry and Su flocks. The application of the new technology, as maintenance of birds in a poultry house with light programme, new hatching apparatuses and improvement of hatching technique resulted in an increase in egg fertilization indices over 90% (Ry, Po, Sł and Ku) and hatching gooslings from the eggs set and eggs fertilized from 80 (Lu) to 86% (Po). (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 34-42